DETERMINANT FACTORS OF STUNTING AMONG CHILDREN AGED 6-24 MONTHS IN THE WORKING AREA OF SUMPIUH I COMMUNITY HEALTH CENTER - Ibnu Zaki; Nadhifia Rahardiani Puspita; Afina Rachma Sulistyaning (POLTEKKES KEMENKES JAYAPURA, 2022)
Stunting is a linear growth disorder due to chronic malnutrition. Various factors influence the incidence of stunting, such as birth weight, birth length, history of maternal weight gain during pregnancy, and history of exclusive breastfeeding. However, study reports show inconsistent results. Therefore this study aims to determine the factors associated with stunting in children aged 6-24 months in the Work Area of the Sumpiuh I Health Center. Factors influencing the incidence of stunting are the history of birth weight, birth length, history of an increase in maternal weight during pregnancy, and history of exclusive breastfeeding. The study used a case-control design with a purposive sampling method. Using a sample of children aged 6-24 months, as many as 64 children. Data collection was obtained from KIA books, interviews, and anthropometric measurements. Data were analyzed using the chi-square test with a significance level (p=0.1). The results showed that there was a significant relationship between birth weight (p=0.083; 90%), birth length (p=0.046; 90%), history of maternal weight during pregnancy (p=0.024; 90%), and history of exclusive breastfeeding ( p = 0.035; 90%) with stunting. Keywords: Birth length, Birth weight, Exclusive breastfeeding, Maternal weight, Stunting